L’Amérique comme destin de l’Europe - Nicolas Garant; Gilbert Larochelle (Cahiers des Amériques Latines)
It is principally in terms of America that the sentiment of decline, at the heart of European thought at the start of the century, defined itself in Ortega y Gasset. His pessimistic analysis of the paradoxical evolution of occidental civilization found a confirmation of sorts in the «American example». However, despite the fact that America appeared to be a prefiguration of coming decadence, Ortega nevertheless refused to accord an important part of the responsibility for its development to the New World. If America is really the destiny of occidental civilization and of Europe, she cannot be the actor.